Peranan Guru dan Orang Tua dalam Mengembangkan Sosial Emosional Anak - Abd. Hakim Naba; Nirwana Nirwana (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2022)
Abstract: The Role of Teachers and Parents in Developing Children's Social Emotional. This study aims to describe the role of teachers and parents in developing children's social and emotional development and describe supporting and inhibiting factors in developing children's social and emotional. This research approach uses a qualitative approach using descriptive qualitative research. The location of the study was carried out by group B Mekka at Tk Islam Al-abrar Makassar City. The data sources in the study were sourced from primary data and skunder data. The data collection techniques in this study are using observation methods, interviews, and documentation methods. The results of this study show that teachers play a very important role in developing children's social and emotional. There is the role of the teacher as an educator, meneger, supervisor, communicator, and motivator. The role of parents in developing children's social and emotional is to instill an attitude of courtesy, foster a sense of responsibility, teach children to always do good, get used to a disciplined life, understand a child's feelings. There are factors that can support and hinder the child's social emotional development. Supporting and inhibiting factors in the child's social emotional development are physical factors, psychological factors and environmental factors of self-confidence..